SIMILARITIES AND DIFFERENCES BETWEEN THE CONCEPTS OF “WEALTH” AND “POVERTY” IN THE ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2025)
This article explores the concepts of «wealth and poverty» through the lens of English and Uzbek linguistics and cultural studies. The concepts of «wealth and poverty» are socio-cultural phenomena; they are reflected in people’s speech behavior, manifested in various types of linguistic units, and distinguished by national specificity. The relevance of this study lies in analyzing the concepts of «wealth and poverty» as key notions in Uzbek and English cultures through an associative experiment.